Wiley revenue recognition + website : - Flood, Joanne M. (Wiley, 2017)
Wiley Revenue Recognition provides an overview of the newrevenue recognition standard and instructs financial statementpreparers step-by-step through the new model, providing numerous,helpful application examples along the way. Readers will grasp themany new disclosures that will be required through the use ofdetailed explanations and useful samples, while electronic toolswill be available to aid the preparer in implementing the standardsand making the proper disclosures.